2019
DOI: 10.1186/s12889-019-7639-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of interventions for an intelligent and individualized mobile health care system to promote healthy diet and physical activity: using an intervention mapping framework

Abstract: Background The mortality of coronary heart disease can be largely reduced by modifying unhealthy lifestyles. However, the long-term effectiveness of interventions for modifying unhealthy diet and physical inactivity of patients with coronary heart disease remain unsatisfactory worldwide. This study aims to systematically design a set of theory-based and evidence-based, individualized, and intelligent interventions for promoting the adoption and maintenance of a healthy diet and physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The contemplation‐action‐maintenance (CAM) model. Reproduced under CCL BY 4.0 from Chen et al (2019) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contemplation‐action‐maintenance (CAM) model. Reproduced under CCL BY 4.0 from Chen et al (2019) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…The contemplation-actionmaintenance (CAM) model. Reproduced under CCL BY 4.0 fromChen et al (2019) [Colour figure can be viewed at wileyonlinelibrary.com] to address their sense of control and their beliefs about perceived symptoms management, since high levels of self-efficacy were reported by CHD patients six to twelve months following their diag-…”
mentioning
confidence: 99%
“…In addition, previous study indicated that the challenges of CHD prevention were the maintenance of healthy behaviors [ 57 ]. The interventions of iCARE study were structured following the CAM model which focused on the moderators and mediators of the action and maintenance stages of behavioral change among patients with CHD [ 42 ]. The utilization of theory-driven interventions in the iCARE study may improve the likelihood of maintaining adherence to health behaviors [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can also access individualized interventions with visual formats (such as animation, video, cartoon, and picture) for facilitating their adherence to health behaviors and medications. The interventions of iCARE -1 were developed based on existing evidence-based health behavior change strategies, and the mediators and moderators identified in the CAM model [ 42 ]. Participants in this group can enter their health-related data into the iCARE -1 by manual entry.…”
Section: Interventionmentioning
confidence: 99%
“…iCARE was designed to address the gaps in conventional interventions, in which multiple CHD-related risk factors were managed through real-time monitoring, person-centered care, and automatic tailored feedback. Following clinical guidelines on CHD secondary prevention [3,30,31], the interventions of iCARE were developed based on the Intervention Mapping framework [32], and the Contemplation-Action-Maintenance (CAM) model [33,34], which was an integrated behavior change model describing the roles of multiple moderators and mediators during the motivation and volition stages that are essential for healthy behavior change and behavior maintenance in individuals with CHD (Multimedia Appendix 1). In our preliminary study, we generated a set of iCARE interventions along with a set of "IF-THEN" algorithms to improve patients' adherence to health behaviors and medications, and conducted a needs assessment on the use of an mHealth-based system among patients with CHD [33].…”
Section: Introductionmentioning
confidence: 99%